The effect of smoking on the outcomes of arthroscopic microfracture for osteochondral lesions of the talus - Gun-Woo Lee; Min-Su Lee; Jong-Eun Kim; Keun-Bae Lee (PLoS ONE, 2025)
Background Smoking is known to negatively affect the outcomes of orthopedic procedures, but its impact on arthroscopic microfracture for osteochondral lesions of the talus (OLT) remains unclear. We aimed to compare clinical outcomes and the status of repaired cartilage following arthroscopic microfracture for small to medium-sized OLT in smokers versus nonsmokers. Methods We enrolled 239 patients (250 ankles), dividing them into smoker (56 patients, 59 ankles) and nonsmoker groups (183 patients, 191 ankles). The primary outcome measure was the FAOS (Foot and Ankle Outcome Score). The AOFAS (American Orthopaedic Foot & Ankle Society) ankle-hindfoot scale, SF-36 PCS (Short Form-36 Physical Component Summary) score, and VAS (Visual Analog Scale) for pain were included as secondary outcomes. Preoperative magnetic resonance imaging (MRI) assessed lesion size, location, and subchondral cyst presence. Postoperative cartilage repair status was evaluated using the Magnetic Resonance Observation of Cartilage Repair Tissue (MOCART) score on 3.0-T MRI. Results The mean OLT sizes were 74.4 mm2 in smokers and 69.9 mm2 in nonsmokers on preoperative MRI. The mean age was 35.9 years in smoker group and 38.8 years in nonsmoker group (p = 0.157). The overall mean follow-up duration was 83.6 months (range, 24–217), with no significant intergroup difference (p = 0.582). There was no significant difference in primary and secondary clinical outcome variables between the two groups at the final follow-up (p > 0.05). In terms of postoperative MRI, 75 ankles (18 smokers, 57 nonsmokers) assessed repaired cartilage status and the mean total MOCART score was significantly lower in smokers (65.0, range 30.0–85.0) compared with nonsmokers (73.7, range 40.0–95.0; p = 0.027). Particularly, the smoker group had significantly lower MOCART scores for surface for repair tissue and signal intensity of the repair tissue variables, respectively (p = 0.019, p = 0.008). Conclusion Although smoker group showed worse status of repaired cartilage on postoperative MRI, the smoker group reported comparable clinical outcomes to those of the nonsmoker group following arthroscopic microfracture for small to medium-sized OLT over a mean follow-up of 7 years. However, caution should be taken in interpreting our conclusion and further larger studies are needed for robust conclusions.